2019
DOI: 10.1038/s41598-019-42057-5
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological testing of allogeneic secretome derived from peripheral mononuclear cells (APOSEC): a novel cell-free therapeutic agent in skin disease

Abstract: A cell-free approach using secretomes derived from stem cells or peripheral blood mononuclear cells is an active area of regenerative medicine that holds promise for therapies. Regulatory authorities classify these secretomes as biological medicinal products, and non- clinical safety assessment thus falls under the scope of ICH S6. A secretome of stressed peripheral blood mononuclear cells (APOSEC) was successfully tested in a toxicology program, supporting clinical use of the new drug candidate. Here, to allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Since allergic reactions to methylene blue treatments have been reported, too high concentrations of methylene blue in the final product represent an exclusion criterion. As safety and tolerability of PBMC secretome have already been demonstrated in our toxicology study [40] and our phase I clinical trial, we consider the presence of methylene blue and other impurities of our secretome as low risk. Taken together, the most appropriate and most meaningful parameters reflecting identity, potency, purity, and safety of each secretome may be determined by extensive drug product characterization and, optionally, after consultation with responsible authorities.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Since allergic reactions to methylene blue treatments have been reported, too high concentrations of methylene blue in the final product represent an exclusion criterion. As safety and tolerability of PBMC secretome have already been demonstrated in our toxicology study [40] and our phase I clinical trial, we consider the presence of methylene blue and other impurities of our secretome as low risk. Taken together, the most appropriate and most meaningful parameters reflecting identity, potency, purity, and safety of each secretome may be determined by extensive drug product characterization and, optionally, after consultation with responsible authorities.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, secretomes may be provided as off-the-shelf products. Toxicity studies for subcutaneous administration of PBMC sec have already been conducted in which subcutaneous injection of PBMC sec was well tolerated [40]. With this in mind, use of cell-free secretomes may be preferable to using cells for therapeutic approaches whenever feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, future clinical studies on damaged tissue will elucidate the full tissue-regenerative efficacy of the PBMC-derived secretome. Since toxicological studies and studies on the viral safety of an allogeneic secretome from γ-irradiated PBMC produced under Good Manufacturing Practice (GMP) conditions have already been successfully conducted, our study paves the way for a first clinical trial in the indication of diabetic foot ulcer 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, efficacy of viral clearance has been demonstrated by Gugerell et al [35]. Moreover, toxicological testing with subcutaneous and intravenous application of PBMC secretome has been performed with no adverse events related to the PBMC secretome [36]. Reproducibility and good manufacturing practice-compliant production of the PBMC secretome have been successfully demonstrated [37] and a phase I clinical trial confirmed pre-clinical findings when no secretome-related adverse events were observed when topically administering autologous irradiated PBMC-derived secretomes in healthy volunteers (ClinicalTrials.gov Identifier: NCT02284360) [38].…”
Section: Introductionmentioning
confidence: 99%